Ag3PO4@Ni3S2 core/shell nanorod arrays for visible light degradation of organic contaminants. (13th March 2019) - Yan, Qian; Su, Yang; Fei, Xiao-Feng; Zhu, Li-Shan; Han, Liu; Hong, Guo; Zhu, Haiguang; Fang, Dong
Abstract: In this study, Ag3 PO4 @Ni3 S2 core/shell nanorod arrays on Ni foam substrate were fabrciated by a method of combining hydrothermal and in situ deposition. The resultant products were characterized by XRD, SEM, UV–vis, XPS and photocurrent response, respectively. The photocatalytic activity of Ag3 PO4 @Ni3 S2 were conducted by photodegradation rhodamine B (RhB) under visible light. The final results confirmed that the photocatalytic activity of Ag3 PO4 @Ni3 S2 samples show an obvious improvement compared with pure Ag3 PO4 . This enhanced performance could be attributed to the fact the charge recombination can be effectively suppressed and the photocorrosion effect of Ag3 PO4 can be inhibited as the photogenerated electrons on the conduction band of Ag3 PO4 can inject to Ni3 S2 . The maximum value of total removal rate were showed in Ag3 PO4 @Ni3 S2 -40 (where 40 represnsents the mass fraction of Ag3 PO4 ), which were 2.12 times than pure Ag3 PO4 . More importantly, the Ag3 PO4 @Ni3 S2 -40 sample exhibits excellent stability under cyclic experiment. A plausible mechanism of photodegradation RhB over Ag3 PO4 @Ni3 S2 sample was also discussed.